TINDAK TUTUR DAN VARIASI BAHASA DALAM FILM WADJDA SEBUAH ANALISIS SOSIOPRAGMATIK (Lisanul Arab: Journal of Arabic Learning and Teaching, 2022)
The objectives of this research are; (1) To find out the directive speech acts used in the Wadjda film; (2) To find out the atmosphere of use, the means of use, who the speakers/users are, the field of use, and the area of ​​use as language variations related to the stigma of Arab ethnicity in the Wadjda film. This research is qualitative research, the research design is in the form of a literature study, the data collection technique is a free-talk-free listening technique, the research instrument uses data cards and data recapitulation sheets, while the data analysis method uses an informal presentation method. In this study, 237 directive speech act data were found which were divided into 55 forms of order; 86 forms of rule; 11 forms of ruling in negation form; 44 forms of advising; 19 forms of pleading; and 22 forms of recommending. The language variation that is highlighted in this study is the variation in terms of female speakers because this film is set in the social background of women's lives in Saudi Arabia.